Quantifying current and potential contributions of Australian indigenous peoples to threatened species management - Leiper, Ian; Zander, Kerstin K.; Robinson, Cathy J.; Carwadine, Josie; Moggridge, Bradley J.; Garnett, Stephen T. (Conservation biology, 2018)
Formal engagement of indigenous peoples in conservation is increasing globally and leads to multiple benefits to communities while contributing to national and international biodiversity goals and obligations. This and ongoing declines in biodiversity have led to calls to increase opportunities for indigenous people to engage in managing their estates. However, there is no overarching understanding of indigenous peoples' involvement in conservation, which limits the identification of new opportunities. We amalgamated information across governments and large nongovernmental organizations in the megadiverse country of Australia to quantify the involvement of indigenous people in management of threatened species. We identified 153 Australian-based projects undertaken by different indigenous groups around the nation in 2015 and 2016 that included explicit funds for management of threatened species or threatened ecosystems. Most were in remote parts of western and northern Australia. Almost one-quarter of all threatened animals and 2% of threatened plants were the subject of some formal conservation action by indigenous people. Occurrence records for 1574 threatened species showed that 823 (89.2%) of 923 species recorded on indigenous peoples' lands were not listed in management projects. This gap may represent new opportunities for conservation initiatives. Because at least 59.5% of Australia's threatened species occur on indigenous peoples' lands, efforts to build appropriate and effective indigenous conservation alliances are vital. However, it is also important to recognize that threatened species are part of complex social, ecological, economic and cultural systems, and to achieve successful outcomes requires consideration of indigenous peoples'priorities, rights, and obligations and relationships with their traditionally owned land and sea. La participación formal de los pueblos nativos en la conservación está creciendo a nivel global, resultando en beneficios múltiples para las comunidades mientras contribuye a las obligaciones y objetivos nacionales e internacionales de biodiversidad. Esto y las continuas declinaciones en la biodiversidad han llevado a llamadas por el incremento de oportunidades para que los pueblos nativos participen en el manejo de sus tierras. Sin embargo, no existe un entendimiento dominante de la intervención de los pueblos nativos en la conservación, lo que limita la identificación de nuevas oportunidades. Amalgamamos la información de gobiernos y organizaciones no-gubernamentales en el país megadiverso de Australia para cuantificar la intervención de los pueblos nativos en el manejo de especies amenazadas. Identificamos 153 proyectos basados en Australia emprendidos por diferentes grupos indígenas en el país entre 2015 y 2016 que incluían un financiamiento explícito para el manejo de especies o ecosistemas amenazados. La mayoría ocurrieron en las partes remotas del norte y oeste de Australia. Casi un cuarto de todos los animales amenazados y el 2% de las plantas amenazadas eran el objetivo de alguna acción formal de conservación realizada por grupos indígenas. Los registros de ocurrencia para 1574 especies amenazadas mostraron que 823 (89.2%) de las 923 especies registradas en tierras pertenecientes a grupos indígenas no aparecían en las listas de los proyectos de manejo. Este vacío puede representar nuevas oportunidades para las iniciativas de conservación. Ya que al menos el 59.5% de las especies amenazadas de Australia están presentes en tierras de grupos indígenas, son vitales los esfuerzos para construir alianzas de conservación efectivas y apropiadas con los pueblos nativos. Sin embargo, también es importante reconocer que las especies amenazadas son parte de complejos sistemas sociales, ecológicos, económicos y culturales, y para obtener resultados exitosos se requiere la consideración de las prioridades, derechos, y obligaciones de los pueblos nativos y sus relaciones con las tierras y mar de propiedad tradicional. 全球范围内, 原住民正越来越多地正式参与到保护当中，这给社区带来许多好处，还有助于达成国 家及全球生物多祥性保护目标和义务。随着生物多祥性不断下降，人们呼吁増加原住民参与管理其居住地的机 会。然而, 目前对原住民参与保护的了解不够全面, 限制了新机会的发现。我们整合了澳大利亚政府和大型非政 府组织的信息, 定量分析了这个生物多祥性大国的原住民在瀕危物种管理中的参与情况。我们确定了 2015 年 和 2016 年全国各地不同的原住民群体在澳大利亚开展的 153个的项目，它们都明确地为濒危物种或瀕危生态 系统管理设立了基金。这些项目大多建立在澳大利亚偏远的西部和北部。原住民正式保护行动的対象包含了澳 大利亚近四分之一的瀕危动物和百分之ニ的濒危植 物。1574 个瀕危物种的出现记录表明，在原住民的土地上 记录到的 923 个物种中有 823 种(89.2%)未被列入管理项目。这ー差距可能也意味着保护计划有新的机会。 由于澳大利亚瀕危物种中至少 59.5% 在原住民的土地有分布，努力建立合适并有效的原住民保护联盟十分重 要。同时还需要认识到，濒危物种是社会、生态、经济和文化的复杂系统中的一部分，要取得保护成果需要考虑 原住民的优先性、权ヵ和义务，以及与他们向来拥有的土地和海洋的关系。